Agricultural trade and trade integration in the East African community - Bouët, Antoine; Nimenya, Nicodème (AKADEMIYA2063, 2023)
The East African Community (EAC) is a regional intergovernmental organization of seven partner states, comprising Burundi, Democratic Republic of the Congo (DRC), Kenya, Rwanda, South Sudan, Tanzania, and Uganda, with its headquarters in Arusha, Tanzania. Like other regional trade agreements (RTAs), the EAC pursues economic and political objectives through regional integration. As Eken (1979) explains, there are two main justifications for regional integration, especially for developing countries. First, for economic reasons, regional integration may provide an important instrument of economic growth. Removing barriers to the free movement of goods, labor, and capital between countries leads to the expansion of trade, and therefore of incomes and employment. Large economic entities with their larger markets (people and space) should permit economies of scale in production, leading to an efficient allocation of resources (capital and labor) and attracting substantial foreign direct investment. Second, for political purposes, establishing regional economic communities (RECs) strengthens collective self-reliance and is therefore expected to reinforce the political independence of groups of countries and enlarge their economic and political role in international relations, a point especially important for developing countries. This chapter addresses five main issues concerning the EAC. It first presents the EAC’s origin and main achievements, and then highlights the EAC’s agricultural trade performance relative to other RECs in Africa by comparing agricultural trade indicators, assessing the composition of trade, and identifying the main destinations/origins of agricultural exports/imports across RECs. This section also compares the level of trade integration in the EAC to that of other African RECs to determine its main agricultural comparative advantages. The same analysis is then repeated at the country level. The following section assesses the magnitude of formal (registered) and informal cross-border agricultural trade within the EAC, discusses the factors of trade integration, and highlights the role of tariff and nontariff measures (NTMs), logistic performance, and exchange rates. The final section offers conclusions.